Comparison of Pulse and Arterial Oxygen Saturation Changes in Endotracheal Suction Opening with Two Sizes of 12 and 14: A Randomised Controlled Trial - Akvan Paymard; Arash Khalili; Mohammad Zoladl; Zahra Zareei; Mostafa Javadi (Hamadan University of Medical Sciences, 2017)
Introduction: Artificial airway stimulates the sympathetic system and the loss of ciliated cells and the accumulation of secretions. Therefore, since these patients do not have the ability to discharge, periodic suction is needed. This study aimed at comparing the effect of open suction endotracheal tube using 2 different sized suction catheters on arterial blood oxygen saturation in critical care ward patients. Methods: In this clinical trial, 36 patients were assigned to one group under suction catheter with two sizes of 12 and 14, respectively. Changes in blood oxygen saturation before, during, after 5 minutes, and 20 minutes after suctioning, were recorded. The data using SPSS version 20 software and ANOVA with repeated measures were analyzed. Results: The results showed that oxygen saturation during small suction catheter was significantly different (P = 0.000). In addition, there was a significant difference in the blood oxygen saturation rate in the first episode (P = 0.000). Five minutes after suctioning, blood oxygen saturation in comparison to 5 minutes before the suction showed no significant difference (P = 0.597), yet blood oxygen saturation 20 minutes after suction in comparison to 5 minutes prior to suctioning and suctioning episodes were significantly different (P = 0.050). Conclusions: Since the fall in endotracheal suctioning of arterial blood oxygen saturation and the reduction in the episodes become more frequent with suctioning, it is recommended to use smaller catheters during suctioning.